CAN ARTIFICIAL INTELLIGENCE (CHATGPT) REPLACE HEALTHCARE PROVIDERS' WORKLOAD IN MANAGING TYPE 2 DIABETES? - Guan, Goh Kian; Amin, Mohd Syazwan Mohd; Azwan, Raja Nurazni Raja (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION ChatGPT is a large language model developed by OpenAI. It provides human-like responses to questions and solves cognitive problems by reinforcing learning via data from online human responses. Diabetes is a chronic illness and information found online can be misleading. This study aims to explore potentials of ChatGPT in providing accurate and patient-friendly diabetes knowledge. METHODOLOGY Open-ended questions pertaining to diabetes pathophysiology, complications, treatment and cure were input into ChatGPT via chat.openai.com platform. Responses were recorded and performance of ChatGPT was graded by two endocrinologists to assess the accuracy of the information. RESULT Overall, artificial intelligence performed well in delivering facts regarding general diabetes knowledge. AI explained in detail the pathophysiology of diabetes, emphasizing the role of insulin in hyperglycaemia. Complications of diabetes were laid out systematically and divided according to the organs involved, though explanations were oversimplified. The approach to treatment of diabetes was clear, where AI explained lifestyle modification followed by differentiating types of medications, including insulin and oral anti-diabetic agents. Errors were detected, such as AI mislabelling SGLT2 inhibitors as injectable medications. Monitoring and follow-up were included. Responses to inquiries regarding diabetes cure were interesting, as AI emphasized the chronic nature of diabetes. It also explored pancreatic transplantation and immunotherapy in type 1 diabetes. CONCLUSION Artificial intelligence has come a long way to provide humanoid responses to questions. It provides accurate information on most diabetes topics with nuances of diabetes educators. There was no inclusion of misinformation rampantly found in social media and web-based platforms. In conclusion, AI can assist healthcare providers in diabetic counselling and education.